Complexifying Individualism Versus Collectivism and West Versus East: Exploring Global Diversity in Perspectives on Self and Other in the Gallup World Poll. (January 2023) - Lomas, Tim; Diego-Rosell, Pablo; Shiba, Koichiro; Standridge, Priscilla; Lee, Matthew T.; Case, Brendan; Lai, Alden Yuanhong; VanderWeele, Tyler J.
A wealth of research has suggested the West tends toward individualism and the East toward collectivism. We explored this topic on an unprecedented scale through two new items in the 2020 Gallup World Poll, involving 121, 207 participants in 116 countries. The first tapped into orientations toward self-care versus other-care ("Do you think people should focus more on taking care of themselves or on taking care of others?"). The second enquired into self-orientation versus other-orientation ("Which of the following is closest to your main purpose in life? Being good at what you do in your daily life, Caring for family and close friends, or Helping other people who need help?"). We anticipated that self-care and self-orientation would index individualism (hence be higher in the West), while other-care and other-orientation would index collectivism (hence be higher in the East). However, contrary to expectation, there was greater self-care in the East (45.82%) than in the West (41.58%). As predicted though, there was greater self-orientation in the West (30.20%) than in the East (23.08.%). Greater self-care in the East invites one of two interpretations. Either these items: (a) index individualism and collectivism as anticipated, so in some ways the East is more individualistic and the West less individualistic than assumed; or (b) do not index individualism and collectivism as anticipated, so the concepts are more complex than often realized (e.g., collectivism may involve prioritizing self-care over other-care). Either way, the findings help complexify these concepts, challenging common cross-cultural generalizations in this area.